2004
DOI: 10.1021/jp048112q
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Visible Light Responses in Anodic Photocurrents at N-Doped TiO2 Film Electrodes

Abstract: Nitrogen doping of anatase TiO2 powder extended the photocurrent action spectrum for water oxidation from the UV-light region (≤400 nm) to the visible-light region (≤ ∼550 nm), as reported. Investigations of the effect of the addition of reductants such as methanol, SCN-, Br-, I-, and hydroquinone to the electrolyte have for the first time given clear experimental evidence to the mechanism that visible-light responses for N-doped TiO2 arise from an N-induced midgap level, formed slightly above the top of the (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
465
5
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(506 citation statements)
references
References 31 publications
30
465
5
6
Order By: Relevance
“…Visible light absorption through the addition of oxygen vacancies was also reported by Martyanov et al [2]. However there now appears to be some agreement regarding the fine electronic details of N doped visible light absorption as reported by Irie [8] and Nakamura [9]. It is now believed that oxygen lattice sites within the TiO 2 crystal are substituted by nitrogen atoms [10,11] form an occupied midgap (N 2p) level above the TiO 2 (O 2p) valence band.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Visible light absorption through the addition of oxygen vacancies was also reported by Martyanov et al [2]. However there now appears to be some agreement regarding the fine electronic details of N doped visible light absorption as reported by Irie [8] and Nakamura [9]. It is now believed that oxygen lattice sites within the TiO 2 crystal are substituted by nitrogen atoms [10,11] form an occupied midgap (N 2p) level above the TiO 2 (O 2p) valence band.…”
Section: Introductionmentioning
confidence: 63%
“…It is now believed that oxygen lattice sites within the TiO 2 crystal are substituted by nitrogen atoms [10,11] form an occupied midgap (N 2p) level above the TiO 2 (O 2p) valence band. The N 2p band therefore acts as a step between the valence and the conduction band of the semiconductor, facilitating excitation of electrons from the N 2p mid-gap band to the conduction band upon irradiation with visible light [8,9]. Titanium dioxide is made up of TiO 6 octahedra [12].…”
Section: Introductionmentioning
confidence: 99%
“…The trapping of electrons effectively increases the lifetime of holes. Non-metallic elements such as nitrogen [9,10], carbon [11,12], sulfur [13], boron [14], and fluorine [15] have been used to impregnate the structure of TiO 2 . It was found that the substitutional carbon dopant incorporated into TiO 2 drastically affected the electronic structure of the material and hence improved its photoactivity due to significant overlap between O 2s 2 2p 4 and the carbon states near the valence band edge [16].…”
Section: Introductionmentioning
confidence: 99%
“…由直线外 推法可知 TS, ATS, NATS2, NATS3, NATS4 带边波长分 别为 385, 402, 408, 410, 419 nm. 根据公式 λ g =1240/E g 可计算出催化剂的禁带宽度 [1] , 式中 λ g 为带边波长(nm), [36,37] .…”
Section: 催化剂的 Uv-vis 光谱unclassified